Work Personality Assessment of Civil Servants (PNS) Using the Analytical Network Process (ANP) Method And Ranting Scale To Determine Achievement Employees At Diskoperindag Aceh Jaya - Amanda, Asril; Sofiyanurriyanti, Sofiyanurriyanti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The Office of Cooperatives, Small and Medium Enterprises, Industry and Trade of Aceh Jaya is an agency engaged in the industrial sector. Assessment of work behavior is one of the most important things in a service or agency that aims to guarantee the objectivity of fostering civil servants (PNS) in terms of assessment to reduce the subjectivity factor. The purpose of this study was to obtain criteria and sub-criteria for assessing the results of the work behavior of civil servants in the industrial sector at the Office of Cooperatives, Small and Medium Enterprises, Industry, Trade in Aceh Jaya, an agency engaged in the industrial sector. The methods used to assess employee performance are the Analytical Network Process (ANP) and Rating Scale methods. The Analytical Network Process (ANP) method is used to weight each criterion and sub-criteria while the rating scale method is used to assess employee work behavior. The results showed that through ANP, the weight of each criterion was obtained, namely service orientation (0.048), integrity (0.05), commitment (0.048), discipline (0.073), cooperation (0.082), leadership (0.071) and community service (0.125). Employees civil servants who are assessed for work behavior using the rating scale method have different values, from the 5 employees the highest score is Employee 4, (4.259907), and the lowest score is employee 1,2,3 and 5 respectively (3 ,7289214). (3.8545035), (3.294166) and (3.916054)Keywords: Work behavior assessment, ANP, Rating Scale.